PT Arino Karya Nusantara Batching Plant Risk Management in Ready-Mix Concrete Business (Journal of Business and Management, 2022)
PT Arino Karya Nusantara is a trading company engaged in construction in the city of Yogyakarta. The company was founded in 2012. In 2021, PT Jor Mix Barokah is divided into two namely PT Jor Mix Barokah and PT Arino Karya Nusantara. PT Arino Karya Nusantara's risk management is still relatively low, this is proven from the percentage of material losses in the manufacturing batching plant for the May-July 2021 period which exceeds 15% according to the standards set by the company, as well as frequent damage to the pan mixer so that it affects the delay and causes great losses to the company. The purpose of this study is to identify other risks that have the potential to occur in the batching plant and assist the company in overcoming the risks that might occur in the batching plant so that there is no greater loss. The method used by this research is the 6x6 scale Probability Impact Matrix (PIM), which is based on the ISO 31000:2018 framework. The conclusion of this study is that there are 22 potential risks in the company batching plant area in Indramayu. 5 risks are classified as extreme risk, 13 risks are classified as severe risk, 3 risks are classified as high risk, and 1 risk is classified as medium risk. In general, there are 6 mitigation plans that must be implemented by PT Arino Karya Nusantara, namely: building an integrated operational information system, improving human resource management, routine maintenance of heavy equipment and software, improving inventory management, conducting better project management, and carry out Corporate Social Responsibility (CSR).Keywords: Risk Management, Ready Mix Concrete Business, Batching Plant, Probability Impact Matrix 6x6 Scale